2018
DOI: 10.3389/fmicb.2018.02710
|View full text |Cite
|
Sign up to set email alerts
|

Putative Nitrogen-Fixing Bacteria Associated With the Rhizosphere and Root Endosphere of Wheat Plants Grown in an Andisol From Southern Chile

Abstract: Acidic ash derived volcanic soils (Andisols) support 50% of cereal production in Chile. Nitrogen (N) is essential for cereal crops and commonly added as urea with consequent environmental concerns due to leaching. Despite the relevance of N to plant growth, few studies have focused on understanding the application, management and ecological role of N2-fixing bacterial populations as tool for improve the N nutrition of cereal crops in Chile. It is known that N2-fixing bacteria commonly inhabits diverse plant co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
61
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 87 publications
(72 citation statements)
references
References 67 publications
9
61
1
1
Order By: Relevance
“…In this study, the bacterial diversity obtained was higher than those reported in wheat rhizobiome studies based on conventional cultivation, which typically report isolates from 14 to 20 bacterial genera (da Moreira et al 2016;Rascovan et al 2016;Verma et al 2015). A recent study focused on screening of putative nitrogen-fixing bacteria associated to wheat plants grown in an Andisols has reported isolation of nine strains belonged to different genera; therefore, the use of MWCs to in situ cultivation methods seems to be an effective alternative to achieve broad of bacterial diversity from wheat microbiome (Rilling et al 2018). Phylogenetically, the three most abundant genera identified were Pseudomonas, Bacillus, and Stenotrophomonas.…”
Section: Discussionmentioning
confidence: 93%
“…In this study, the bacterial diversity obtained was higher than those reported in wheat rhizobiome studies based on conventional cultivation, which typically report isolates from 14 to 20 bacterial genera (da Moreira et al 2016;Rascovan et al 2016;Verma et al 2015). A recent study focused on screening of putative nitrogen-fixing bacteria associated to wheat plants grown in an Andisols has reported isolation of nine strains belonged to different genera; therefore, the use of MWCs to in situ cultivation methods seems to be an effective alternative to achieve broad of bacterial diversity from wheat microbiome (Rilling et al 2018). Phylogenetically, the three most abundant genera identified were Pseudomonas, Bacillus, and Stenotrophomonas.…”
Section: Discussionmentioning
confidence: 93%
“…The members of the genus Burkholderia occur simultaneously with fungal taxa (Stopnisek et al, 2015), and the co-occurring might be due to Burkholderia's ability to migrate with the growing hyphae (Nazir et al, 2012). Mycobacterium has nitrogen fixation functions (Rilling et al, 2018) and can provide nitrogen for the growth of R. griseocarnosa. Sorangium has rich xylan-degrading enzymes that can degrade biological macromolecules, cellulose, hemicellulose, and xylan (Tamaru et al, 2010), which is beneficial for increased mushroom productivity (Zhou et al, 2017).…”
Section: Keystone Species and Ecological Functionsmentioning
confidence: 99%
“…The PS protocol has been shown to improve the culturability of a wide range of microorganisms, including slow-growing heterotrophs (Kato et al, 2018), hard-to-culture Actinobacteria (Adam et al, 2018), and alkane-degrading bacteria (Zheng et al, 2018). Furthermore, many research groups reported the isolation of novel bacterial taxa using the PS protocol (Nishioka et al, 2016;Huang et al, 2017;Kitzinger et al, 2018;Rilling et al, 2018). However, these studies only targeted aerobic microorganisms.…”
mentioning
confidence: 99%